2014
DOI: 10.3390/md12084311
|View full text |Cite
|
Sign up to set email alerts
|

Marinopyrrole Derivatives with Sulfide Spacers as Selective Disruptors of Mcl-1 Binding to Pro-Apoptotic Protein Bim

Abstract: A series of novel marinopyrroles with sulfide and sulphone spacers were designed and synthesized. Their activity to disrupt the binding of the pro-apoptotic protein, Bim, to the pro-survival proteins, Mcl-1 and Bcl-xL, was evaluated using ELISA assays. Fluorescence-quenching (FQ) assays confirmed the direct binding of marinopyrroles to Mcl-1. Benzyl- and benzyl methoxy-containing sulfide derivatives 4 and 5 were highly potent dual Mcl-1/Bim and Bcl-xL/Bim disruptors (IC50 values of 600 and 700 nM), whereas car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 38 publications
(68 reference statements)
1
18
0
Order By: Relevance
“…Various manipulations to 28 and some of its synthetic precursors have allowed access to multiple analogues for SAR studies. 64,65,69,70 The first, and thus far only, synthesis of marinopyrrole B (29) was reported in 2013 by Cheng et al (not shown), whereby the bipyrrole core in this case was instead generated through alkylation of a trihalogenated pyrrole, which underwent further manipulations to complete a Paal-Knorr construction of the second pyrrole ring, a precursor which allowed for the generation of rac-29. 71 Scheme 5: Convergent total synthesis of racemic marinopyrrole A (28).…”
Section: Marinopyrroles: Determination Of Enzymatically-imposed Atropmentioning
confidence: 99%
“…Various manipulations to 28 and some of its synthetic precursors have allowed access to multiple analogues for SAR studies. 64,65,69,70 The first, and thus far only, synthesis of marinopyrrole B (29) was reported in 2013 by Cheng et al (not shown), whereby the bipyrrole core in this case was instead generated through alkylation of a trihalogenated pyrrole, which underwent further manipulations to complete a Paal-Knorr construction of the second pyrrole ring, a precursor which allowed for the generation of rac-29. 71 Scheme 5: Convergent total synthesis of racemic marinopyrrole A (28).…”
Section: Marinopyrroles: Determination Of Enzymatically-imposed Atropmentioning
confidence: 99%
“…Marinopyrrole derivatives, 29 , 30 , 34 – 36 , 38 , 39 , 41 , 43–46 were inactive at decreasing Mcl-1 levels and at inducing caspase 3 cleavage at concentrations as high as 10 μM (data not shown). As we have reported previously, none of the sulfides or sulphone derivatives are active at the 3 μM concentration; however, at higher concentrations (40 μM) some of the sulfide and sulphone derivatives are cell-active [40]. …”
Section: Resultsmentioning
confidence: 85%
“…Marinopyrrole 23 [35], the bistrifluoromethyl derivative of 1, exhibited similar potency to that of 1 against Mcl-1/Bim complex and was slightly more potent against Bcl-xL/Bim complex. Nonsymmetrical marinopyrroles with either chlorine [39] or fluorine [40] substitution in ring B (47 to 52) showed that chlorine in either 3′ or 4′ position improves potency against both Mcl-1 and Bcl-xL. Chlorine in position 5′ improves potency against Mcl-1 but not Bcl-xL.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…26 More recently, a series of target-guided screening and SAR programs have identified ligation of Mcl-1, indicating that indeed marinopyrrole A binds to Mcl-1. 27 However, the targeting of Mcl-1 was not observed by others through use of additional models including the screening of cell lines with altered Mcl-1 expression. 28 It should be emphasized that marinopyrrole is a potent electrophile that readily adds nucleophilic residues in proteins by displacement of chlorine.…”
Section: Case Study 2: the Marinopyrroles Target Actinmentioning
confidence: 98%